RELATIONSHIP OF SANITATION AND SOCIO ECONOMIC STATUS OF PARENTS TO CARIES SEVERITY - Putri Bestari Ilvani Thine; Isnur Hatta; Rosihan Adhani (Dentino: Jurnal Kedokteran Gigi, 2024)
Background: Riskesdas stated the prevalence of caries in children aged 5-9 years in Indonesia in 2018 was 92.6%. External caries factors consist of environment, behavior, health services, and heredity. The physical environment is one of the health environments that contributes the most to health status, including dental and oral health. Sanitation with the Community-Based Total Sanitation (STBM) program is part of the physical environment. The STBM pillars consist of: stopping open defecation, washing hands with soap, drinking water and food management, waste management, and liquid waste management. Behavioral predisposing factors include parents' socioeconomic status which is determined by education, occupation, and income. Socioeconomic status affects the ability of parents to care for their children's teeth. Purpose: To analyze the relationship between sanitation and socioeconomic status of parents on the severity of caries in kindergarten children. Methods: This research is an analytic observational study with a cross-sectional method. The respondents of this study were 49 children of TK Al Hidayah in Mandiangin Barat Village, Banjar Regency, South Kalimantan Province. Data collection includes questionnaires and the def-t assessment sheet. Results: Spearman correlation test p=0.435 showed no relationship between sanitation and caries severity. Spearman correlation test p=0.0001 showed that there was a relationship between the socioeconomic status of parents and the severity of caries. The correlation coefficient -0.519 indicates a medium strength relationship in the opposite direction. Conclusion: There is no relationship between sanitation and caries severity. There is a relationship between the socioeconomic status of parents with the severity of caries.  Keywords: def-t index, Socio-economic, STBM.